Endoscopic treatment of an acute fistula after laparoscopic sleeve gastrectomy - De Simone, Federico; Dorelo, Rodrigo; Machado, Pablo (Cirugía del Uruguay, 2022)
Acute gastric fistula is one of the main complications associated with laparoscopic vertical gastrectomy (LVG). There are multiple therapeutic options for its resolution, being endoscopic treatment by placing clips or stents one of the most important. The applicability of each method will depend on the type of fistula and the patient's condition. We present the case of a 35-year-old woman who developed an acute fistula after LGV. Endoscopic treatment is performed with placement of the over-the-scope clip system (Ovesco®) at the level of the fistulous orifice, with subsequent placement of a self-expanding metal stent.